MACROECONOMIC ANALYSIS OF THE INDONESIAN NICKEL INDUSTRY USING DEPEST ANALYSIS - Pauline H.Pattyranie Tan (Ultima Management : Jurnal Ilmu Manajemen, 2022)
Abstract- The global push to accelerate the electric car industry is expected to increase world demand for nickel until 2030. Indonesia is the largest producer, with a Nickel production of 800,000 tons, or 30% of the world supply. The Indonesian government then responded to this global situation by issuing a law banning the export of 1.8% low-grade Nickel, in line with its policy of accelerating the national Strategic Project (PSN), focusing on nickel downstream (besides downstream other minerals and coal) to increase added value to strengthen the competitiveness of the national nickel industry on an international scale, suppressing imports and also creating energy independence. In an effort to achieve this downstream, it is necessary to carry out a macroeconomic analysis of the various opportunities and challenges faced in developing the Indonesian Nickel industry. This external analysis is the analysis Demography factors, Economy, Political, Ecological, and Social Technology (DEPEST). The results show: 1) Southeast Sulawesi has a demographic bonus with a low unemployment rate and the potential to be trained in trade and mining. 2) In terms of economic factors, Southeast Sulawesi Nickel has quite large reserves, and the LQ showed that the mining and quarrying sector has the highest comparative advantage compared to other basic sectors. 3) So far government regulations are accelerating the provision of added value to domestically manufactured products by relying on domestic raw materials. 4) The impact on socio-culture is to increase the community’s welfare around the mining area as long as it is carried out while maintaining environmental sustainability. 5) There is a promising technology for downstream Nickel. Keywords: Nickel Industry; Smelter; DEPEST Analysis